Taufiqul Hakim â€œAmtsilatiâ€ dan Pengajaran Nahwu-sharaf - M Misbah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
One of skill becoming goals in study Arabic Ianguage reading skill. Someone wish to reach it must mastering various interconnected knowledge, among others Nahwu â€“Sharaf. This knowledge becomes burden to one whom studying it especially for beginner. This because the huge number of items exist in Nahwu-Sharaf, so that need very long time to mastering it. This Items effectiveness and time efficiency represent the problem in Nahwu-Sharaf learning. These matters become Taufiqul Hakimâ€™s study materials and concern. Finally he found one new format of efficient and effective method and items in learning Nahwu-Sharaf. The Items compiled in his books entitled â€œBuku Amtsilatiâ€ and his method knows as Amtsilati Method. The application of Amtsilati Method in Nahwu â€“ Sharaf learning emphasize the student activeness, with rather few theory but much practice and also delivering items start from easy then gradually reaching difficult ones.